The influence of language dominance and domain-general executive control on semantic context effects. Issue 7 (2nd September 2021) - Boned, Jaume; Cardona, Gemma; Jefferies, Elizabeth; Hernández, Mireia
ABSTRACT: We investigated whether semantic context effects in speech production and comprehension are sensitive to language dominance and whether they involve domain-general executive control. We indexed these effects using semantic blocking within the cyclical semantic paradigm (corresponding to poorer performance in semantically related contexts compared to unrelated contexts) in a study that addressed the limitations of previous research: (i) we compared semantic blocking between participants tested in their native language and those tested in a language they were clearly less proficient in (not just the less dominant language), and (ii) we examined the involvement of executive control with a non-linguistic (rather than a linguistic) index. Participants in both groups showed equal semantic blocking in production and comprehension. Executive control only predicted the magnitude of semantic blocking in speech production. These results suggest that semantic context effects are insensitive to language dominance, and that effects of executive control arise in production tasks.